Mexiterpes Sabinus, New Genus and New Species, a Mexican Troglobite (Diplopoda: Trichopetalidae) - Nell B. Causey (Psyche: A Journal of Entomology)
This troglobitic milliped is of unusual interest because it is the type of a new genus and the first Mexican record of the family Trichopetalidae, which previously has been known from Nova Scotia to Louisiana, Oklahoma, and Colorado. If the genus has undergone speciation as related genera have, then additional species and subspecies will be found in other Mexican caves. Other millipeds from Mexican caves have been described by R. V. Chamberlin (1942).